DEVELOPMENT OF REALISTIC MATHEMATICAL LEARNING DEVELOPMENT OF STATISTICS MATERIAL IN CLASS IX SMP NEGERI 3 PAREPARE - Andi Rusdi (Universitas Negeri Makassar, 2013)
The purpose of this research is to develop learning tools in mathematics learning using realistic mathematics learning in Class IX SMP, with this tool is expected to change the paradigm of learning